Arbitrase dalam Penyelesaian Sengketa Bisnis Internasional - Endah Trihandayani (Jurnal Hukum Lex Generalis, 2025)
International business disputes are increasing in line with the development of trade between countries. The resolution of cross-border legal disputes through national courts often faces various obstacles, so international arbitration is a widely recognized alternative solution. This study analyzes the role of arbitration as an international business dispute resolution mechanism and the legal options used in international arbitration. Arbitration is one of the mechanisms for resolving international business disputes that tends to be chosen over the courts because of its advantages which include confidentiality, trust from business people, the expertise of arbitrators, and a fast and final process. In international arbitration, the parties have the freedom to determine the applicable law.